I‘jaz al-Qur’an sebagai mukjizat abadi: Kajian konseptual tentang fungsi dan dimensi kemukjizatan Al-Qur’an. - Syarhatushshadriyyah Syarha; Abdul Aziz; Ahmad Rivan Zahri; Riska Sawitri (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2026)
The study of i'jaz al-Qur'an is an important part of Qur'anic studies that discusses the miraculous nature of the Qur'an as proof of the prophethood of the Prophet Muhammad (peace be upon him). This study aims to analyze the meaning of i'jaz, the function of the miraculous nature of the Qur'an, various views of scholars, aspects of miraculousness, the position and uniqueness of the Qur'an as an eternal miracle, and the differences between the miracles of the Qur'an and those of previous prophets. This study employs a qualitative method with a library research approach. The results of the study show that i'jaz al-Qur'an is clear evidence of the truth of Islam, which includes linguistic aspects (al-i'jaz al-bayani), scientific aspects (al-i'jaz al-'ilmi), legislative aspects (al-i'jaz al-tasyri'i), and supernatural aspects (al-i'jaz al-ghaibi). This miraculous nature confirms the inability of humans to match the Qur'an and proves the truth of the message of the Prophet Muhammad SAW. In addition to serving as proof of prophethood and strengthening faith, i'jaz al-Qur'an also becomes an epistemological basis for the integration of revelation and reason. The Qur'an's status as an eternal miracle distinguishes it from the miracles of previous prophets, which were temporal in nature